Dihydroisotanshinone I combined with radiation inhibits the migration ability of prostate cancer cells through DNA damage and CCL2 pathway - I-Yun Lee; Yin-Yin Lin; Yao-Hsu Yang; Yu-Shin Lin; Chun-Liang Lin; Wei-Yu Lin; Yu-Ching Cheng; Li-Hsin Shu; Ching-Yuan Wu (BMC, 2018)
Abstract Background Radiotherapy plays an important role in the treatment of prostate cancer. Despite that sophisticated techniques of radiotherapy and radiation combined with chemotherapy were applied to the patients, some tumors may recur. Therefore, the study investigated the effect of dihydroisotanshinone I (DT) and the combination treatment of 5 μM DT and 5Gy irradiation (IR) against the migration ability of prostate cancer cells. Methods DT and the combination treatment were studied for its biological activity against migration ability of prostate cancer cells with transwell migration assay. Subsequently, we tried to explore the underlying mechanism with ELISA, flow cytometry and Western's blotting assay. Results The results showed that DT and the combination treatment substantially inhibited the migration ability of prostate cancer cells. DT and the combined treatment can decrease the ability of macrophages to recruit prostate cancer cells. Mechanistically, DT and the combination treatment reduced the secretion of chemokine (C-C Motif) Ligand 2 (CCL2) from prostate cancer cells. We also found that DT treatment induced the cell cycle of prostate cancer cells entering S phase and increased the protein expression of DNA damage response proteins (rH2AX and phosphorylated ataxia telangiectasia-mutated [ATM]) in DU145 cells and PC-3 cells. Conclusions DT displays radiosensitization and antimigration effects in prostate cancer cells by inducing DNA damage and inhibiting CCL2 secretion. We suggest that DT can be used as a novel antimetastatic cancer drug or radiosensitizer in the armamentarium of prostate cancer management.